1992
DOI: 10.3177/jnsv.38.15
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Orally Adiministered Ergosterol and 7-Dehydrocholesterol in Rats and Lack of Evidence for Their Vitamin D Biological Activity.

Abstract: SummaryMetabolism of orally administered ergosterol (Erg) and 7 -dehydrocholesterol (7-DHC) in rats and their vitamin D biological ac tivity were investigated. Most of orally administered Erg and 7-DHC were excreted in feces and the remaining sterols were absorbed through intestine. The absorbed sterols were not transported in skin as the intact forms but metabolized into brassicasterol and cholesterol, respectively, within 25h. Neither increment of intestinal calcium absorption nor plasma calcium concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 14 publications
0
16
2
Order By: Relevance
“…Our earlier studies in Rora (Labeo rohita) have shown that fish deficient in vitamin D (vitamin D-deficiency was judged by the absence of any detectable vitamin D in the liver of fish, grown in darkness and fed a diet devoid of vitamin D for six months) showed no significant differences in the vitamin D-related (bone and carcass mineral stores) and growth (carcass protein and lipid, hepatosomatic index, feed efficiency, and mortality rates) parameters when compared with the controls fed vitamin D3, suggesting that this vitamin may not be an essential nutrient for fishes (27). This observation is contrary to similar studies in terrestrial verte brates, where decreased calcification of bone and hypocalcemia is the classical manifestation of vitamin D deficiency (28)(29)(30).…”
Section: Discussioncontrasting
confidence: 66%
“…Our earlier studies in Rora (Labeo rohita) have shown that fish deficient in vitamin D (vitamin D-deficiency was judged by the absence of any detectable vitamin D in the liver of fish, grown in darkness and fed a diet devoid of vitamin D for six months) showed no significant differences in the vitamin D-related (bone and carcass mineral stores) and growth (carcass protein and lipid, hepatosomatic index, feed efficiency, and mortality rates) parameters when compared with the controls fed vitamin D3, suggesting that this vitamin may not be an essential nutrient for fishes (27). This observation is contrary to similar studies in terrestrial verte brates, where decreased calcification of bone and hypocalcemia is the classical manifestation of vitamin D deficiency (28)(29)(30).…”
Section: Discussioncontrasting
confidence: 66%
“…23) Therefore, orally consumed ergosterol derivative 9(11)-DHEP would most likely impact on colon cancer, which is known to be related to diet. Therefore, we investigated the effect of 9(11)-DHEP on the growth of HT29 human colon adenocarcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…37) Kobori et al suggested that orally administered EPO in edible mushrooms might have a protective effect against colon cancer, and reported it possesses a suppressive effect against HT-29, CACO-2 human colorectal cancer cell lines, including the action mechanism.…”
mentioning
confidence: 99%